Special Classes of Ternary Semirings - A. Rajeswari (Mathematics and Computer Science: Contemporary Developments Vol. 3, 2024)
Studied the concept of mono-ternary semirings which is the special class of Ternary Semirings. If T is mono-tenary semiring and lateral singular then T is singular, weakly separative, and regular ternary semigroups. Proved identities related to mono-ternary semirings and characterize these ternary semirings. Ternary structures rise certain hopes in view of their applications in physics and other related sciences.